Proteomic study of human umbilical vein endothelial cells in culture - Sanjiv Sharma (PROTEOMICS, 2003)
The endothelium is a single layer of cells lining the inside face of all blood vessels. It constitutes a major metabolic organ which is critically involved in the generation and the regulation of multiple physiological and pathological processes such as coagulation, hemostasis, inflammation, atherosclerosis, angiogenesis and cancerous metastasis dissemination. In order to increase our knowledge about the protein content and the main biological pathways of human vascular endothelial cells, we have undertaken the proteomic analysis of the most explored present endothelial cell model, i.e. primocultures of human umbilical vein endothelial cells (HUVECs). Using low levels of protein loads (~ 30 νg), the association of two-dimensional electrophoresis with matrix-assisted laser desorption/ionization-time of flight mass spectrometry, liquid chromatography-tandem mass spectrometry and database interrogations allowed us to identify 53 proteins of suspected endothelial origin in quiescent HUVECs. Beside cytoskeletal proteins such as actin, tubulin, tropomyosin and vimentin, we identified various proteins more especially implicated in cellular motility and plasticity (e.g. cofilin, F-actin capping protein and prefoldin), in regulation of apoptosis and senescence (protease inhibitor 9, glucose related proteins, heat shock proteins, thioredoxin peroxidase, nucleophosmin) as well as other proteins implicated in coagulation (annexin V, high mobility group protein), antigen presentation (valosin containing protein and ubiquitin carboxyl terminal hydrolase isozyme L1) and enzymatic capabilities (glutathione-S-transferase, protein disulfide isomerases, lactate deshydrogenase). The presented annotated 2-D maps of HUVECs will be soon available on the web at http://www. huvec.com.